Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Tingkat Kecemasan Pada Pasien Pre Operasi Di Rumah Sakit - Aisah; Ernauli Meliyana; Lisna Nuryanti; Sismanto, Bayu Aji (Jurnal Keperawatan Nusantara, 2025)
Background: Anxiety is an excessive and unclear feeling of worry, and it is also a response to both external and internal stimuli that causes emotional, cognitive, physical, and behavioral symptoms. Anxiety is different from fear because, in fear, the object is clearly known and threatens the well-being of the person, while in anxiety, the object is unknown. Anxiety is an experience that everyone goes through (universal) throughout their life. Anxiety has a positive function because it can motivate people to take actions that can resolve their issues. Anxiety is considered normal when it is proportionate to the situation and will disappear once the situation is resolved. Objective: To determine the effect of the deep breathing relaxation technique on anxiety levels in pre-operative patients at the hospital. Methods: This study uses a pre-experimental design, quantitative correlation, with primary data from pre-operative patients aged 17-50 years, consisting of 126 respondents. Sampling was calculated using Slovin's formula. Data collection was done using a questionnaire and interviews with the Hamilton Anxiety Rating Scale (HARS). Results: From the 126 respondents, 14 (11.1%) had no anxiety, 51 (40.5%) had mild anxiety, 58 (46.0%) had moderate anxiety, and 3 (2.4%) had severe anxiety. The Chi-square statistical test showed a p-value of 0.000 (p <0.05), indicating that there is an effect of the deep breathing relaxation technique on anxiety levels in pre-operative patients at the hospital. Conclusion: There is an effect of the deep breathing relaxation technique on anxiety levels in pre-operative patients at the hospital (p=0.000).